Analisis Penerapan Prinsip Good Corporate Governance (GCG) Pada PT Bank Mandiri (Persero) Tbk - Febrianti Shakira; Hastiani Nasution; Ahmad Wahyudi Zein (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at PT Bank Mandiri (Persero) Tbk as one of the state-owned banks that plays a strategic role in the Indonesian banking system. The implementation of GCG is crucial in maintaining public trust, improving performance, and ensuring business sustainability in the banking sector. This research employs a qualitative method with a descriptive approach, focusing on secondary data analysis obtained from annual reports, corporate governance reports, sustainability reports, and official information published on the website of PT Bank Mandiri (Persero) Tbk. The results indicate that Bank Mandiri has consistently implemented the principles of transparency, accountability, responsibility, independency, and fairness in its corporate governance system. These principles are reflected in information disclosure practices, clear organizational structures, regulatory compliance, independent decision-making processes, and fair treatment of all stakeholders. Overall, the implementation of GCG at PT Bank Mandiri (Persero) Tbk contributes positively to strengthening internal control systems, enhancing public trust, and supporting the stability and sustainability of banking operations.